Inhibition of Notch3 prevents monocrotaline-induced pulmonary arterial hypertension. (14th September 2015) - Zhang, Yonghong; Xie, Xinming; Zhu, Yanting; Liu, Lu; Feng, Wei; Pan, Yilin; Zhai, Cui; Ke, Rui; Li, Shaojun; Song, Yang; Fan, Yuncun; Fan, Fenling; et al.
ABSTRACT: It has been shown that activation of Notch3 signaling is involved in the development of pulmonary arterial hypertension (PAH) by stimulating pulmonary arteries remodeling, while the molecular mechanisms underlying this are still largely unknown. The aims of this study are to address these issues. Monocrotaline dramatically increased right ventricle systolic pressure to 39.0 ± 2.6 mmHg and right ventricle hypertrophy index to 53.4 ± 5.3% ( P < 0.05 versus control) in rats, these were accompanied with significantly increased proliferation and reduced apoptosis of pulmonary vascular cells as well as pulmonary arteries remodeling. Treatment of PAH model with specific Notch inhibitor DAPT significantly reduced right ventricle systolic pressure to 26.6 ± 1.3 mmHg and right ventricle hypertrophy index to 33.5 ± 2.6% ( P < 0.05 versus PAH), suppressed proliferation and enhanced apoptosis of pulmonary vascular cells as well as inhibited pulmonary arteries remodeling. Our results further indicated that level of Notch3 protein and NICD3 were increased in MCT-induced model of PAH, this was accompanied with elevation of Skp2 and Hes1 protein level and reduction of P27Kip1. Administration of rats with DAPT-prevented MCT induced these changes. Our results suggest that Notch3 signaling activation stimulated pulmonary vascular cells proliferation by Skp2-and Hes1-mediated P27Kip1 reduction, and Notch3 might be a new target to treat PAH.